Novel Mo-modified medium entropy alloys achieving enhanced corrosion resistance in acidic solution. (15th May 2023) - Pan, Zhimin; Luo, Hong; Zhao, Qiancheng; Cheng, Hongxu; Wang, Xuefei; Ma, Yicong; Li, Xiaogang
Abstract: The effect of Mo addition on corrosion behavior of (CoNiV)100−x Mox medium entropy alloys (MEAs) in 0.5 M H2 SO4 solution was investigated. Results revealed that the introduction of Mo element by micro alloying can significantly improve the corrosion resistance of CoNiV MEA, despite the precipitation of the second phase. Besides, the competition effect between microgalvanic coupling and micro alloying in dominating the corrosion resistance of (CoNiV)100−x Mox MEAs was discussed in detail. Graphical Abstract: ga1 Highlights: Mo addition ameliorates the corrosion resistance of (CoNiV)100−x Mox medium-entropy alloys (MEAs). Semiconductor properties and chemical compositions of the passive film are studied. The competition effect between microgalvanic coupling and micro alloying in dominating the corrosion resistance is discussed. The pitting and corrosion resistance mechanisms of (CoNiV)100−x Mox MEAs are clarified.